2014
DOI: 10.1242/jeb.109991
|View full text |Cite
|
Sign up to set email alerts
|

Do all frogs swim alike? The effect of ecological specialization on swimming kinematics in frogs

Abstract: Frog locomotion has attracted wide scientific interest because of the unusual and derived morphology of the frog pelvic girdle and hind limb. Previous authors have suggested that the design of the frog locomotor system evolved towards a specialized jumping morphology early in the radiation of the group. However, data on locomotion in frogs are biased towards a few groups and most of the ecological and functional diversity remains unexplored. Here, we examine the kinematics of swimming in eight species of frog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…; Gurdon & Hopwood, ; Burggren & Warburton, ; Wheeler & Brändli, ; Harland & Grainger, ; Cline & Kelly, ; Clemente & Richards, ; Richards & Clemente, ; Robovská‐Havelková et al. ; Burgess, ). Xenopus laevis is easy to house and maintain, and its eggs and embryos are large, tolerate manipulation and are produced in large quantities (Wheeler & Brändli, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gurdon & Hopwood, ; Burggren & Warburton, ; Wheeler & Brändli, ; Harland & Grainger, ; Cline & Kelly, ; Clemente & Richards, ; Richards & Clemente, ; Robovská‐Havelková et al. ; Burgess, ). Xenopus laevis is easy to house and maintain, and its eggs and embryos are large, tolerate manipulation and are produced in large quantities (Wheeler & Brändli, ).…”
Section: Introductionmentioning
confidence: 99%
“…The African clawed frog, Xenopus laevis Daudin, 1802, is one of the most widely used organisms in biological research, including applications in cell and molecular biology, genetics, physiology, embryology, development and morphogenesis, neuroscience, biomechanics, toxicology and medicine (Gurdon et al 1971;Gurdon & Hopwood, 2000;Burggren & Warburton, 2007;Wheeler & Br€ andli, 2009;Harland & Grainger, 2011;Cline & Kelly, 2012;Robovsk a-Havelkov a et al 2014;Burgess, 2016). Xenopus laevis is easy to house and maintain, and its eggs and embryos are large, tolerate manipulation and are produced in large quantities (Wheeler & Br€ andli, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kolesová et al 2007;Královec et al 2010;Roček et al 2015), functional morphology (e.g. Delfino et al 2009;Přikryl et al 2009;Robovská-Havelková et al 2014) and classical descriptive and systematic palaeontology (e.g. Roček 2008;Wuttke et al 2012;Dong et al 2013;Roček et al 2014).…”
Section: Biographical Sketch and Commentary On The Academic Contributmentioning
confidence: 99%
“…). Anteroposterior translation has also been shown during swimming (Videler and Jorna, ; Robovska‐Havelkova et al, ), however, the focus of this study is to investigate the pelvic function during terrestrial jumping locomotion. Recent phylogenetic reviews of a suite of pelvic traits across Anura have shown that the “lateral‐bender” configuration is both basal and generalized for walker/hoppers, whereas the rod‐like “sagittal hinge” configuration has appeared independently multiple times within several crown group neobatrachian anurans (Reilly and Jorgensen, ; Jorgensen and Reilly, ).…”
Section: Introductionmentioning
confidence: 99%
“…1). Anteroposterior translation has also been shown during swimming (Videler and Jorna, 1985;Robovska-Havelkova et al, 2014), however, the focus of this study is to investigate the pelvic function during terrestrial jumping locomotion. Recent phylogenetic reviews of a suite of pelvic traits across Anura have shown that the "lateral-bender" configuration is both basal and generalized for walker/hoppers, Fig.…”
Section: Introductionmentioning
confidence: 99%